2015
DOI: 10.1093/neuonc/nov106
|View full text |Cite
|
Sign up to set email alerts
|

pH-weighted molecular imaging of gliomas using amine chemical exchange saturation transfer MRI

Abstract: Results suggest pH-weighted MRI may provide new insight into brain tumor physiology beyond traditional imaging technologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
88
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 100 publications
(93 citation statements)
references
References 30 publications
5
88
0
Order By: Relevance
“…pH imaging, which is a cutting‐edge application of CEST, may become a potential marker of hypoxia . A recent study showed the promising result of amine‐proton based CEST images, which focuses on 3 ppm, in detecting intratumoral pH changes . However, this effect is somewhat confusing in the assessment of brain tumor with APT images; high‐grade tumors with high proliferation activity can show acidotic changes due to anaerobic metabolism or necrosis, which causes a lactate peak in MRS .…”
Section: Discussionmentioning
confidence: 99%
“…pH imaging, which is a cutting‐edge application of CEST, may become a potential marker of hypoxia . A recent study showed the promising result of amine‐proton based CEST images, which focuses on 3 ppm, in detecting intratumoral pH changes . However, this effect is somewhat confusing in the assessment of brain tumor with APT images; high‐grade tumors with high proliferation activity can show acidotic changes due to anaerobic metabolism or necrosis, which causes a lactate peak in MRS .…”
Section: Discussionmentioning
confidence: 99%
“…Exploratory MRI techniques such as chemical exchange saturation transfer provide new methods of generating tumor contrast and can be used to interrogate variables such as pH, acidity, lactate levels, and other aspects of cellular metabolism and microenvironment (Harris et al, 2015, 2016; Longo et al, 2016). Chemical exchange saturation transfer has been used to distinguish recurrence from radiation necrosis in a pilot prospective study of 16 patients with brain metastases treated with SRS (Mehrabian et al, 2017).…”
Section: Caveats To Interpreting Posttreatment Imaging Changesmentioning
confidence: 99%
“…The chemical exchange between amine and amide protons in bulk water has been shown to be pH dependent using a new imaging method called CEST imaging . The inherently elevated concentration of glutamine within tumors further increases the available proton exchange, resulting in a higher CEST signal at 3.0 ppm . The combination of increased protons (low pH) and increased glutamine makes pH‐weighted MRI using CEST contrast from amine protons on glutamine particularly attractive as a noninvasive tool for assessment of microenvironment acidity within malignant brain tumors.…”
Section: Introductionmentioning
confidence: 99%